(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article provides information on the criteria of order for the development of Independent Education, independent work, competency approach, creative creativity, research, logical thinking in the process of continuous professional development of pedagogical personnel. Model requirements for the use of innovative technologies and methods for independent education are described.